REALITAS KEKERASAN PEKERJA PEREMPUAN DAN KONSEKUENSI PERLINDUNGAN HUKUM - Ida Bagoes Mantra; Kasto Kasto; Abdul Haris (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2001)
This study deals with Indonesian female workers migration especially on the case of workers security and workers violence. The study is carried out at Cilacap Regency with the research samples in Donan, Jojog and Kuta Waru Vilage in the area of Central Cilacap sub-district. This study is design to explore the phenomena of international female workers migration regarding the security and violence issues in the whole of migration process. The value of this research is desired to be raw material, which is, can be a positive requirement in formulating the role of international migration policy. The facts shows that the program of international labor sending since 1980s was lacked of security that can be protecting migrant workers, especially female migrants. This condition causes that Indonesian (female) migrants tend to be marginal workers in destination countries.